ANALISIS BEBAN KERJA KARYAWAN PADA PT XYZ DENGAN METODE WORKLOAD ANALYSIS (WLA) DAN WORKFORCE ANALYSIS (WFA) - Laela Azini Novitasari (2023)
PT. XYZ is an active company in the Packaged Drinking Water sector. The company faces issues with excessive working hours and the inability of the factory to meet all demands. Therefore, the objective of this research is to estimate the workload of each worker using Work Load Analysis and Work Force Analysis methods, in order to determine the optimal number of workers that corresponds to the workload. Furthermore, a cost analysis will be conducted to support decisionmaking. The analysis results indicate that all operators experience excessive workload at all workstations, with workload calculations exceeding the normal limit of 100%. Hence. Based on the calculations using the Work Force Analysis method, it is recommended that PT. XYZ adds 3 workers. The allocation of workers is as follows: 1 person in the cup packing section, 1 person in the palette packing section, and 1 person in the curtain section. From the cost analysis results, the alternative with the lowest cost is recommended, adds 3 workers with a cost of Rp. 14.885.928